PENGARUH PENGUASAAN OPERASI BILANGAN TERHADAP HASILBELAJAR EKONOMI MAKRO PADA MATERI POKOK PENDAPATAN NASIONAL MAHASISWA SEMETER V V PROGRAM STUDI PENDIDIKAN EKONOMI STKIP âTAPANULI SELATANâ PADANGSIDIMPUAN - Fauzi, stkiptap (JURNAL EDUCATION AND DEVELOPMENT, 2016)
This research purpose is to see the correlation between general journal mastery and studentsâ accountancy learning result in trial balance  at the tenth grade in Program Studi Pendidikan Ekonomi STKIP âTapanuli Selatanâ Padangsidimpuan.Population in this research are all the students of  fiveth grade in Program Studi Pendidikan Ekonomi STKIP âTapanuli Selatanâ Padangsidimpuan, consists of 3 classes with total 120 students. The population uses random sampling technique, so the total of sample are 40 students. To get the needingâs data, the writer took the test with multiple choise with 20 item from each variable. Then, the result of this research was made with two steps. The first step with inferential analyses, to know the shadow about special journal mastery with studentsâ accountancy learning result in numeral operation mastery. The second step by using descriptive analyses, to certain the hypothesis given by using correlation formula ârâ product moment by Pearson.From the result of this research gotten avarage of national income mastery on 72,10. If interpreted in result criteria. It was on âgoodâ category. Meanwhile studentsâ accountancy learning result on trial balance have average 78,04. It was on âgoodâ category. From the result of analyse on certaining hypothesis gotten t-test 6,56 and t-table 2, 05 on  free sign (dk) 40-2=38 on believing sign 95% with false degree 5%. So that, it was known that t-account bigger with t-table, that is 6,56>2,05, so the alternative of hypothesis is accepted. The  means, there is significant correlation between general journal mastery and studentsâ accountancy learning result in trial special journal at the tenth grade in Program Studi Pendidikan Ekonomi STKIP âTapanuli Selatanâ Padangsidimpuan.